The first pass metabolism of nifedipine in man. - Waller, D G (1984)
Oral administration of nifedipine (20 and 30 mg tablets) to six volunteers was associated with a bioavailability of 0.43 and the presence of its nitropyridine analogue in the plasma. This metabolite was present in only trace amounts in samples taken from the same volunteers following i.v. administration of nifedipine. The peak plasma concentrations and area under the plasma concentration-time curve suggest that the nitropyridine analogue is a major, first pass, metabolite of nifedipine.